(untitled) (The All Results Journal, 2013)
Degenerate levels of 13C-incorporation have been the biggest obstacle for mass spectrometry assisted assignment of 13C-dimethylamine resonances in nuclear magnetic resonance spectroscopy (NMR). Three methods are shown here to break the degeneracy in 13C-labeling of lysozyme. Reductive methylation of lysozyme in the presence of 18-crown-6-ether is shown to hinder methylation but not in a selective manner. The use of multiple reducing agents ranging in strength and hydrophobicity proved to alter reaction rates in hydrophobic areas but labeling was still degenerate within error. The development of a non-destructive Edman degradation to remove the problematic N-terminal lysine for the assignment of NMR resonances associated with both α- and ε-dimethylamines proved elusive.